Effect of organic and inorganic fertiusers on the growth, yield and nutritional quality of choy sum (Brassica Rapa Var Parachinensis) - Wong, Han Yee (2016)
Soil fertility is essential for sustainable crop production. Inorganic fertilisers are expensive and do not bring excellent crop production in the long term. Combined application of different fertiliser sources can act as an alternative way to overcome this problem. A study was carried out at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah Sandakan Campus, in order to determine the effect of organic and inorganic fertiliser on the growth, yield and nutritional quality of choy sum (Brassica rapa var parachinensis). The treatments used were full recommended rate of compound NPK fertiliser (340 kg ha-1), full recommended rate of poultry manure fertiliser (PM) (20 t hal), combination of half recommended rate of NPK fertiliser and full recommended rate of poultry manure (170 kg NPK ha-1 + 20 t PM ha-1), combination of full rate NPK and half rate poultry manure (340 kg NPK ha-1 + 10 t PM ha-1), combination of half rate NPK and half rate poultry manure (170 kg NPK ha-1 + 10 t PM ha-1) and control (without amendment). The experiment was laid out in a randomized complete block design (RCBD) with five replicates per treatment. Parameters studied were plant height (cm), stem girth (cm), number of leaves, leaf length (cm), leaf width (cm), fresh weight of shoot (g/plant), dry weight of shoot (g/plant) and vitamin C content (mg/100g). The treatment means were compared by Least Significant Differences (LSD) at 5% probability level. Results revealed that, at harvesting day, there were only significant differences on growth of choy sum in terms of stem girth and leaf length among the different treatments. Highest stem girth (7.5 cm), leaf length (9.0 cm), leaf width (6.1 em), leaf number (25), fresh weight (39.0g/plant) and dry weight (4.2 g/plant) of shoot were obtained from choy sum subjected to T5, combination of full NPK and half PM (340 kg ha-1 + 10 t ha-1). Further, T2, full NPK (340 kg ha-1) produced the highest plant height (24.6 cm) of the choy sum whereas T3, full PM (20 t ha-1) showed the highest vitamin C content (50.0 mg/100g) in the choy sum. Thus, it could be stated that combination of organic and inorganic fertilizer is beneficial for the growth and yield of choy sum while vitamin C content of choy sum is dependent only on the organic fertiliser dose. Treatments which consist of combination of full recommended rate of NPK and half recommended rate of PM (340 kg NPK ha-1 + 10 t PM ha-1) can be recommended for farmers to increase choy sum production and also reduce the cost of cultivation.